Implementation of Integrated E-Governance Methodologies and Practices in Developing Economies for Effective Governance and Project Management - Ayub Ahmed Sultan, Khan Mohamed (Digital Repository of Theses, 2025)
This study explores the adoption and implementation of e-governance in developing countries, where digital governance has the potential to enhance transparency, accountability, and citizen participation, while improving the efficiency and effectiveness of government services. Despite successes in developed nations, the implementation of egovernance in developing countries faces significant challenges, including infrastructural limitations, digital divides, bureaucratic resistance, and socio-cultural constraints. While existing literature offers recommendations to address these challenges, a key issue remains the lack of an integrated e-governance structure and appropriate revenue models, which negatively impact adoption. This gap in research, particularly in the context of developing nations, has prompted this study to focus on integrated e-governance best practices and relevant revenue models. The study evaluates the current state of egovernance in developing countries, identifies the challenges, and proposes strategies for improvement using a mixed-methods approach, combining both qualitative and quantitative data. It draws on stakeholder experiences and case studies to explore the implementation of integrated e-governance systems in developing economies. It identifies key components of successful e-governance approaches and assesses their effectiveness. The study finds that technological infrastructure, digital literacy, and institutional capacity are critical factors influencing the success of e-governance, while subjective attitudes and social norms play a significant role in shaping public engagement with digital platforms. In conclusion, this study provides insights into the current state of e-governance in developing countries, identifying key challenges such as technological infrastructure, digital literacy, and institutional capacity. It highlights the critical role of attitudes and social norms in driving e-governance adoption, emphasizing the importance of fostering positive perceptions and social support, and recommends strategies to overcome these barriers, including targeted awareness campaigns, capacity-building initiatives, and stakeholder engagement activities. Additionally, it suggests revenue models like Public- Private Partnerships and taxation to enhance the financial sustainability of e-governance systems. The findings not only offer practical recommendations for implementing integrated e-governance structures but also open new avenues for future research. Further studies are needed to explore how these strategies can be tailored to the specific governance ecosystems of other developing countries, considering their unique challenges and characteristics. This research paves the way for extending e-governance practices to economically weaker areas, identifying region-specific strategies to address obstacles and improve implementation.